Fusion of Biological Membranes and Related Problems - Hilderson, Herwig.; Fuller, Stephen. (Subcellular Biochemistry, 2002)
Membrane fusion and targeting processes are tightly regulated and coordinated. Dozens of proteins, originating from both the cytoplasm and membranes are involved. The discovery of homologous proteins from yeast to neurons validates a unified view. Although much is known about the interfering proteins, the events occurring when two lipid bilayers actually fuse are less clear. It should be remembered that lipid bilayers behave like soap-bubbles fusing when meeting each other. In this respect interfering proteins should be considered as preventing undesirable and unnecessary fusion and eventually directing the biological membrane fusion process (when, where, how, and overcoming the activation energy). In this latest volume in the renowned Subcellular Biochemistry series, some aspects of fusion of biological membranes as well as related problems are presented. Although not complete, there is a lot of recent information including on virus-induced membrane fusion. The contributors of the chapters are all among the researchers who performed many of the pioneering studies in the field.